The Evolution of Germany’s Response to The 2015 Syrian Refugee Crisis - Fayad, Maya (2019)
The thesis examines the evolution of Germany’s refugee policy in light of the 2015 massive refugee influx. This influx gave rise to a severe crisis, dominating headlines and engendering a raging political debate. Asylum seekers at that time originated mainly from Syria, Afghanistan, and Iraq, escaping war and persecution. Germany’s dynamic role in managing the refugee crisis has gained considerable attention globally. For a short period of time, between late August and mid-November 2015, Germany liberalized its refugee policy by admitting a substantial number of refugees without restrictions. However, beginning September 2015, the country executed a near-reversal on this welcoming policy approach by calling for EU-level quotas on the number of refugees entering Europe as a whole, and a cutback on the number of refugees Germany would admit. In addition to investigating the reasons and underlying motivations for the implementation of an open-door refugee policy and the subsequent policy reversal, this thesis also interprets how the country’s decision to backtrack on the liberal policy rapidly, knowing that plenty of people were still escaping the Syrian civil war, represents a puzzle for the constructivist and realist theories which do not entirely explain this real world example. Accordingly, the thesis investigates the underlying motives for the German government to pursue a liberal refugee policy approach and the reasons behind the quick reversal, by focusing on the changing interests, beliefs, as well as the set of norms that the actors involved in the refugee policy decision-making in Germany were following.